The Edinburgh history of Scottish literature. - Brown, Ian, 1951-; Clancy, Thomas Owen; Manning, Susan, 1953-2013; Pittock, Murray (Edinburgh History of Scottish Literature EUP., 2007)
In almost a century since the First World War ended, Scotland has been transformed in many rich ways. Its literature has been an essential part of that transformation. The third volume of the History, /i> explores the vibrancy of modern Scottish literature in all its forms and languages. Giving full credit to writing in Gaelic and by the Scottish diaspora, it brings together the best contemporary critical insights from three continents. It provides an accessible and refreshing picture of both the varieties of Scottish literatures and the kaleidoscopic versions of Scotland that mark literary developments since 1918. The other volumes in the History are: The Edinburgh History of Scottish Literature, Volume 1: From Columba to the Union (until 1707) The Edinburgh History of Scottish Literature, Volume 2: Enlightenment, Britain and Empire (1707-1918) Key Features Original - presents new approaches to what is literature and what is Scottishness. Inclusive - Gaelic and diasporic writing, Latin writing, theological writing, legal writing, and context chapters. Comprehensive - provides the fullest coverage of Scottish literature ever and the first survey for almost 20 years. Distinguished contributors from many countries. Influences the agenda for critical debate on Scottish writing in the twenty-first century.